Long read sequencing reveals transgene concatemerization and vector sequences integration following AAV-driven electroporation of CRISPR RNP complexes in mouse zygotes - Luqman, Muhammad W.; Jenjaroenpun, Piroon; Spathos, Jessica; Shingte, Nikhil; Cummins, Mitchell; Nimsamer, Pattaraporn; Ittner, Lars M.; Wongsurawat, Thidathip; Delerue, Fabien (Frontiers in Genome Editing, 2025)
Over the last decade CRISPR gene editing has been successfully used to streamline the generation of animal models for biomedical research purposes. However, one limitation to its use is the potential occurrence of on-target mutations that may be detrimental or otherwise unintended. These bystander mutations are often undetected using conventional genotyping methods. The use of Adeno-Associated Viruses (AAVs) to bring donor templates in zygotes is currently being deployed by transgenic cores around the world to generate knock-ins with large transgenes (i.e., 1–4 kb payloads). Thanks to a high level of efficiency and the relative ease to establish this technique, it recently became a method of choice for transgenic laboratories. However, a thorough analysis of the editing outcomes following this method is yet to be developed. To this end, we generated three different types of integration using AAVs in two different murine genes (i.e., Ace2 and Foxg1) and employed Oxford Nanopore Technologies long read sequencing to analyze the outcomes. Using a workflow that includes Cas9 enrichment and adaptive sampling, we showed that unintended on-target mutations, including duplication events and integration of viral sequences (sometimes reported using other workflows) can occur when using AAVs. This work highlights the importance of in-depth validation of the mutant lines generated and informs the uptake of this new method.